Perceraian Di Bawah Tangan Dan Akibat Hukumnya: Studi Kasus Di Kelurahan Karijawa Kecamatan Dompu Kabupaten Dompu - Kholvi, Nifa; Arifin Dilaga, Zaenal (Faculty of Law, University of Mataram, 2024)
This research aims to identify the factors and legal consequences of non-judicial divorce, as well as solutions for its eradication among the community in Karijawa Village, Dompu District. The research conducted is empirical. The findings indicate that economic factors are the most dominant influence on the occurrence of unofficial divorce. This is evident as the majority of the community in Karijawa Village falls into the low-income category, with most of them working as laborers. The legal consequences have a significant impact on the rights of children and wives. Post-divorce, husbands are often absolved of any responsibility to support their children or ex-wives. Furthermore, it impacts the legal status of the divorce itself.